Investigating the relationship between psychological adjustment and the quality of marital relationship dimensions of women with breast cancer in Golestan Province in 2022 - Elham Khoori; Fatemeh Torklalebaq; Mitra Reyhani; Najimeh Tarkesh Esfahani (Clinical Epidemiology and Global Health, 2024)
Introduction: Breast cancer is the most prevalent cancer among women. Contracting this cancer is an experience accompanied by extreme mental stress. Therefore, when they know about their disease, they experience high levels of disappointment and weakness in adapting to it in their personal and family lives. Like any other type of cancer, it endangers various aspects of mental health, including the marital relation. Breast cancer diagnosis is a crisis in a women's life. In this respect, mastectomy (i.e., breast removal surgery) is eliminating a part of the body that symbolizes gender, femininity, and maternal dimensions. Regarding the importance of the breast in forming a woman's sexual identity, the reaction to the disease by women may involve fear, anxiety, and depression. Hence, the contraction of breast cancer may damage the married life of these women. The present study was conducted to explore the relationship between mental adjustment to cancer (MAC) and marital relationship quality (MRQ) in women with breast cancer. Materials and method: This descriptive-correlational study was conducted on a sample size of 135. Sampling was performed through the accessible sampling method on women with breast cancer referred to two clinics in Gorgan City during 2020–2021. The data-collection tool comprised the demographic data blank, the Mini-Mac mental-adjustment-to-cancer questionnaire, and the Perceived Relationship Quality Component (PRQC) inventory. The data were analyzed using Pearson's correlation index, multivariable regression model, and the SPSS software ver. 18. Results: The mean scores for MAC and MRQ domains in women with breast cancer were 81.15 ± 19.78 and 93.19 ± 95.17, respectively. There was a direct and significant relation between the MAC score in women with breast cancer and the perceived MRQ in them (r = 0.341; p = 0.001), such that with increasing the psychological MAC, the perceived quality of the marital relationship was significantly higher. Conclusion: Based on the obtained results, it is inferred that with an increase in the MAC, MRQ domains improve accordingly. Concerning the major role of the MRQ in the mental health of couples, the authorities must prepare a service package to improve the MRQ and mental health of breast cancer patients.